1971
DOI: 10.1295/polymj.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Further Test of the Two-Parameter Theory of Dilute Polymer Solutions: Poly(p-bromostyrene)

Abstract: ABSTRACT:Light-scattering and intrinsic-viscosity data are presented for fractions of po1y(p-bromostyrene) in monochlorobenzene and dioxane at 30°C, and in benzene at temperatures ranging from 25 to 50°C. The theta temperature for this polymer in benzene is 26.3°C. With the data for the statistical-radius expansion factor as and the interpenetration function 1f! appearing in the second virial coefficient, the agreement between theory and experiment is examined with respect to the same two criteria as those emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1972
1972
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…For polystyrene in cyclohexane the transition is purported102,103 to lead to a Kq value at 40 °C, which is lower than that found under conditions. Suffice it to state that these findings103-105 are not supported by valid theory2 nor by extensive data36, 41,44,53,54,[57][58][59]61,63,65,[104][105][106][107][108][109][110][111][112][113] for various solvent-polymer systems on the temperature dependence of intrinsic viscosity, second virial coefficient, chain dimensions, and diffusion coefficients near the temperature.…”
Section: Resultsmentioning
confidence: 97%
“…For polystyrene in cyclohexane the transition is purported102,103 to lead to a Kq value at 40 °C, which is lower than that found under conditions. Suffice it to state that these findings103-105 are not supported by valid theory2 nor by extensive data36, 41,44,53,54,[57][58][59]61,63,65,[104][105][106][107][108][109][110][111][112][113] for various solvent-polymer systems on the temperature dependence of intrinsic viscosity, second virial coefficient, chain dimensions, and diffusion coefficients near the temperature.…”
Section: Resultsmentioning
confidence: 97%
“…81. In this paper, we use light-scattering and viscosity data obtained recently by our group82 for monodisperse polystyrenes (prepared anionically in tetrahydrofuran) to test the theory following our procedure.…”
Section: Comparison With Experimentsmentioning
confidence: 99%
“…Over the past few decades numerous researchers reported on the formation and physicochemical properties of poly(4-bromostyrene) (PBrS) and its copolymers. These studies have been motivated by excellent flame-retarding properties and unique phase behavior of PBrS. A variety of synthetic methodologies for obtaining homopolymers and copolymers of bromostyrene have been described, including free radical, , cationic, , anionic, and controlled radical polymerization . In addition, the synthesis of random copolymers, poly(styrene- co -4-bromostyrene) (PBr x S), comprising styrene and 4-bromostyrene units, has been reported that utilized bromination reaction performed on parent polystyrene (PS) coils. The latter reaction has several advantages.…”
Section: Introductionmentioning
confidence: 99%